Mortality and Paclitaxel-Coated Devices: An Individual Patient Data Meta-Analysis. Issue 23 (9th June 2020) - Rocha-Singh, Krishna J.; Duval, Sue; Jaff, Michael R.; Schneider, Peter A.; Ansel, Gary M.; Lyden, Sean P.; Mullin, Christopher M.; Ioannidis, John P.A.; Misra, Sanjay; Tzafriri, Abraham R.; Edelman, Elazer R.; Granada, Juan F.; et al.
Abstract : Background: Paclitaxel-containing devices (PTXDs) significantly reduce reintervention in patients with symptomatic femoropopliteal peripheral artery disease. A recent aggregate-data meta-analysis reported increased late mortality in patients with peripheral artery disease treated with PTXDs. We performed an individual patient data meta-analysis to evaluate mortality. Methods: Manufacturers of US Food and Drug Administration–approved and commercially available devices in the United States provided deidentified individual patient data for independent analysis. Cox proportional hazards 1-stage meta-analysis models using intention-to-treat methods were used for the primary analysis. A secondary analysis of recovered missing vital status data was performed. The impact of control crossover to PTXDs, cause-specific mortality, and drug dose mortality were assessed. Results: A total of 2185 subjects and 386 deaths from 8 PTXD trials with 4-year median follow-up were identified. The primary analysis indicated a 38% (95% CI, 6% to 80%) increased relative mortality risk, corresponding to 4.6% absolute increase, at 5 years associated with PTXD use. Control and treatment arm loss to follow-up and withdrawal were 24% and 23%, respectively. With inclusion of recovered vital status data, the excess relative mortality risk was 27% (95% CI, 3%–58%). This observation was consistent across various scenarios, including as-treated analyses, with no evidence of increased risk over time with PTXDs. Mortality risk tended to be increased for all major causes of death. There were no subgroup differences. No drug dose–mortality association was identified. Conclusions: This individual patient data meta-analysis, based on the most complete available data set of mortality events from PTXD randomized controlled trials, identified an absolute 4.6% increased mortality risk associated with PTXD use. Abstract : Supplemental Digital Content is available in the text.